Determination of Surface Roughness and Accuracy of Alginate Impression Material Disinfected by Immersion - Hummudi, Israa M; Mansoor, Nidhal S (Journal of Baghdad College of Dentistry, 2022)
Background: This study was conducted to evaluate the surface roughness and dimensional accuracy of commercially obtainable alginate impression material in terms of imbibition after immersion in two different media. Materials and method: Two disinfecting agents, ethanol 70% and povidone-iodine 4%, were used to access the dimensional accuracy and surface roughness of alginate impression material. Weights of specimen discs of alginate impressions were measured before and immediately after immersion to gain a measure of imbibition. For surface roughness, disinfected specimens rectangle was examined before and after disinfection. Results: Minimal changes in weight were observed after disinfection, but a statistically non-significant difference was found before and after immersion. It did not affect the surface roughness of alginate impression material Conclusion: Disinfection of alginate impression material with ethanol and povidone iodine had no significant effect on dimensional accuracy and surface roughness.